(untitled) (Analele Universității București. Limba și literatură română, 2025)
The word Bogrie in the Occitan language, Bougrie in the Oïl language, Bulgaria in Latin, entered French literature between 1198 and 1213, when Pope Innocent III called for the fourth crusade in the East, this from August 15, 1198, and against the Albigensians, in the West, in 1207-1208. The term is used in French by Robert de Clari and by Geoffroy de Villehardouin in their respective accounts of the conquest of Constantinople in 1204; then in Occitan by William of Tuledo and his anonymous successor in the Canso de la Crosada, the Song of the Albigensian Crusade between 1208 and 1219; and, finally, in Latin, in their chronicles, by Pierre des Vaux de Cernay and by William of Puylaurens, two witnesses of these events. The expression arises again in literature, in France and in Central and Eastern Europe, from 1965. How was “Bougrie”, medieval Bulgaria, evoked in these writings, by historians and writers, as a land of heresies, dissidences, different beliefs and abrupt amalgams?